PEMANFAATAN LIMBAH ORGANIK SERABUT KELAPA MENJADI MEDIA TANAM COCOPEAT DI DESA AIK PRAPA - Aisyah Fauzani, Ramy; Ilyasa, Fikriadin; Perwira Hadi, Akbar; Aini, Ru’yatul; Alexander Siahaya, Patrick; Mayani, Erna; Enjeli, Dea; Santatakaori, Ni Putu; Fadillah, Abramo; Alpinesta, Nur; Nuriadi, Nuriadi (Universitas Mataram, 2025)
The community service program conducted by KKN students from Mataram University in Aik Prapa Village, Aikmel District, Lombok Timur, aims to address the issue of coconut fiber waste. This program focuses on utilizing this organic waste to create cocopeat, an eco-friendly planting medium that enhances agricultural productivity. Through surveys, the KKN students identified the negative impacts caused by the accumulation of coconut fiber waste on the local environment. This innovative solution involves socialization activities to educate the community about the benefits of cocopeat, including its excellent water retention capacity and nutrient-rich properties. Practical demonstrations engaged villagers in the production and application of cocopeat in local gardens and agricultural practices. The results showed a positive response from the community, highlighting increased awareness and participation in sustainable agricultural practices. This KKN program not only provides a solution for waste management but also encourages collaboration among community members to promote environmental sustainability and economic development in Aik Prapa Village.